Restriction Enzyme Mapping of MC4R Gene in Bligon Goat Using Bioedit Program - Latifah, Latifah; Priyadi, Dwi Ahmad; Maharani, Dyah; Kustantinah, Kustantinah; Hartatik, Tety (2017)
Restriction enzymes are a fundamental tool of molecular biology for determination of diversity and in vivo function. Many research used restriction enzyme for genotyping mammals based on MC4R gene. The objective this study to map the restriction enzyme of MC4R gene in Bligon goat. The mapping of restriction enzyme on MC4R gene was carried in Bligon goat (n=10). MC4R gene was amplified using specific primer forward and reverse, resulting 642 bp of amplification products. We discovered 5 enzymes (FatI, NlaIII, RsaI, Acc651 and KpnI) which recognized 2 SNPs region based on restriction mapping using Bioedit program. There were three recommended enzymes (RsaI, Acc651 and KpnI) for genotyping the Bligon goat. In the present study, an individual with CC genotype produced 2 fragments with enzyme RsaI and 1 fragment with Acc651 and KpnI. An individual with CT genotype produced 4 fragments with enzyme RsaI and 3 fragments with Acc651 and KpnI. In conclusion, we suggested that restriction enzymes RsaI, Acc651 and Kpn1 may be used for genotyping of a targeted gene using PCR-RFLP method for Bligon goat in the future research.